2019
DOI: 10.1116/1.5087255
|View full text |Cite
|
Sign up to set email alerts
|

Plasma jet based in situ reduction of copper oxide in direct write printing

Abstract: Printing of nanostructured films with tailored oxidation state and electronic structure can have far reaching applications in several areas including printable electronics, optoelectronics, solar cells, catalytic conversion, and others. Widely used inkjet/aerosol/screen printing techniques require pre- and postprocessing for enhanced adhesion and tailoring of the chemical state of the thin film. Herein, we demonstrate atmospheric pressure plasma jet printing with unique capability to print and tune in situ the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…This extra step is time consuming, inconvenient and results in additional thermal budget but more importantly, could preclude the use of delicate substrates depending on the annealing temperature. In contrast, combining cold plasma with aerosol delivery of the ink/nanoparticles can eliminate the need for the secondary annealing step [31][32][33] and also, the use of atmospheric pressure plasma in the form of a dielectric barrier discharge (DBD) eliminates the need for the expensive vacuum chamber construction and vacuum pumps, thus simplifying the overall system. The characteristics of the plasma jet can be exploited to tailor the properties of the materials passing through it.…”
Section: Ubiquitous Deployment Of Various Functional Devices Inmentioning
confidence: 99%
See 1 more Smart Citation
“…This extra step is time consuming, inconvenient and results in additional thermal budget but more importantly, could preclude the use of delicate substrates depending on the annealing temperature. In contrast, combining cold plasma with aerosol delivery of the ink/nanoparticles can eliminate the need for the secondary annealing step [31][32][33] and also, the use of atmospheric pressure plasma in the form of a dielectric barrier discharge (DBD) eliminates the need for the expensive vacuum chamber construction and vacuum pumps, thus simplifying the overall system. The characteristics of the plasma jet can be exploited to tailor the properties of the materials passing through it.…”
Section: Ubiquitous Deployment Of Various Functional Devices Inmentioning
confidence: 99%
“…The material properties including oxidation state, electronic conductivity, dielectric properties and others can be tailored in situ through this printing process. The plasma offers several advantages [31][32][33] including i)…”
Section: Ubiquitous Deployment Of Various Functional Devices Inmentioning
confidence: 99%
“…Patterned-wettability technology is important for manipulating fluid on a surface and applications [21][22][23][24]. Among different patterning techniques, atmospheric-pressure plasma jet (APPJ) has been demonstrated as an efficient tool for patterned modifications on different surfaces, such as polycarbonate (PC) [25], polypropylene (PP) [26], polyethylene terephthalate (PET) [27], polymethyl methacrylate (PMMA) [28], polydimethylsiloxane (PDMS) [29] and even metallic surfaces [30][31][32]. The surface modification with an APPJ has been applied to different applications.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Others have deposited copper from various sources but used a high-power radiofrequency (RF) discharge. [12][13][14] Dey et al [15] used an ambient pressure dielectric barrier discharge (DBD) jet with copper oxide nanoparticles as a copper source. We previously reported that ambient air low-temperature (<40°C) PECVD of polymer films can be achieved by using a floating-electrode helium dielectric barrier discharge jet (He DBD jet).…”
Section: Introductionmentioning
confidence: 99%